SECONDARY SCHOOL STUDENTS' CONCEPT OF INFINITY: PRIMARY AND SECONDARY INTUITIONS - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2009)
The concept of infinity has an important place in secondary and higher education curricula. The aim of this study is to investigate primary and secondary intuitions of Turkish primary school students in relation to the concept of infinity as well as to determine to what extent schooling is successful in the attainment of the concept of infinity. Qualitative research techniques were used in this study. Data collection included open-ended questionnaires conducted with 131 primary school students aged 13-14 and semi-structured interviews with ten of these students. The data were analysed by categorisation. Results indicated that students' personal experiences mainly determined their concept of infinity, and that formal education had minimal, effects. Some misconceptions were also found to exist.